Impacts of drought in the primary sector of the Central American Dry Corridor - Calvo-Solano, Oscar David (2018)
Central America has suffered the impact of several extreme hydrometeorological events, among which drought stands out. This has had adverse effects of different kinds in the region known as the Central American Dry Corridor (CSC, in Spanish). The objective of this work was to describe the impacts that agriculture, livestock and economy of the CSC countries have suffered due to droughts: agricultural, hydrological and socioeconomic. A review of primary and secondary sources was carried out, such as scientific articles, press reports and studies reports from national and international institutions. The most recurrent impacts are at the level of basic grains and cattle, also due in part to the ENSO (El Niño-Southern Oscillation) phenomenon. Because the CSC is a region with high vulnerability to drought and other extreme hydrometeorological events, it is necessary to carry out an adequate characterization of the CSC taking as a baseline similar studies like this one, that orginate a discussion process for the design and implementation of strategies and anticipated public policies of adaptation and mitigation of the drought in the CSC and therefore, lead to improve the quality of life of its population.